2008
DOI: 10.1002/rcm.3371
|View full text |Cite
|
Sign up to set email alerts
|

Towards the electrospray ionization mass spectrometry ionization efficiency scale of organic compounds

Abstract: An approach that allows setting up under predefined ionization conditions a rugged self-consistent quantitative experimental scale of electrospray ionization (ESI) efficiencies of organic compounds is presented. By ESI ionization efficiency (IE) we mean the efficiency of generating gas-phase ions from analyte molecules or ions in the ESI source. The approach is based on measurement of relative ionization efficiency (RIE) of two compounds (B 1 and B 2 ) by infusing a solution containing both compounds at known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
100
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(106 citation statements)
references
References 22 publications
(36 reference statements)
4
100
2
Order By: Relevance
“…They concluded that analytes need to have a large enough nonpolar area to move to the surface of the droplet and also a structural element that allows charging (protonation, deprotonation, adduct formation, etc.). This tendency was also confirmed by Leito et al [17] based on a study of esters and aromatic amines. Ehrmann et al [21] tried to predict analyte signal in ESI/MS and observed the best predicting power while using the solution phase basicity of analyte (pK b ).…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…They concluded that analytes need to have a large enough nonpolar area to move to the surface of the droplet and also a structural element that allows charging (protonation, deprotonation, adduct formation, etc.). This tendency was also confirmed by Leito et al [17] based on a study of esters and aromatic amines. Ehrmann et al [21] tried to predict analyte signal in ESI/MS and observed the best predicting power while using the solution phase basicity of analyte (pK b ).…”
Section: Introductionsupporting
confidence: 69%
“…As the evaluation of absolute IEs is difficult if not impossible, the term relative ionization efficiency (RIE) has been introduced [17] (see Formula 1 in Experimental).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of ESI are complex and numerous studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] have been carried out for its elucidation. It has been shown that the electrospray ionization efficiency (IE) [16] of an analyte is influenced by its molecular structure as well as the solvent (including its pH and additives) and the MS system. Despite intense research, the mechanisms of ESI are not fully understood.…”
Section: E Lectrospray Ionization Mass-spectrometry (Esi/ms) Is Amentioning
confidence: 99%
“…In order to withdraw the influence of the instrument (as well as numerous other influencing factors) a relative measurement approach has been proposed [16], whereby every measurement essentially compares the IE of two compounds simultaneously in the same solution. An extensive IE scale in the positive ion mode has been compiled with this approach [7].…”
Section: E Lectrospray Ionization Mass-spectrometry (Esi/ms) Is Amentioning
confidence: 99%
See 1 more Smart Citation